Islamic Educational Leadership and Teacher Performance in Indonesian State Islamic Primary Schools - Putri, Anita; Patimah, Siti; Murtafiah, Nurul Hidayati; Abg. Abu Nawas, Abg. Ashmirul; Ahad, Ijaz (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
Leadership quality in Islamic primary education is central to teacher professionalism, yet empirical evidence from Indonesian state madrasahs remains limited. This qualitative multi-site case study examines how Islamic school principals manage leadership practices and how these practices relate to teacher performance in three State Islamic Primary Schools (Madrasah Ibtidaiyah Negeri/MIN) in Lampung, Indonesia. Data were derived from observations, semi-structured interviews with principals and teachers, and institutional documents during May-June 2024; analysis followed data reduction, display, and verification with source, technique, and time triangulation. Findings show that leadership management operated through four connected functions: participatory planning, role-based organizing, motivational implementation, and continuous supervision. Teacher performance was reflected in lesson planning, curriculum enactment, classroom management, innovative pedagogy, assessment, individual feedback, character formation, and professional learning. Cross-site patterns indicate a participative-relational model in MIN 2 Pesawaran, an innovation-performance model in MIN 2 Bandar Lampung, and an exemplary-spiritual model in MIN 3 Lampung Selatan. Supportive factors included collaborative climate, parental/committee support, and teacher commitment; constraints included limited funding, administrative workload, unequal ICT access, and teacher rotation. The study contributes a context-sensitive model of Islamic educational leadership for teacher performance and inclusive quality education.